An Analysis of the Efficiency of the Educational Management of the Academic Cooperation Project between the Department of Local Administration and Suan Dusit University: Data Envelopment Analysis - Muangmoon, Saisamorn; Tangchitcharoenkhul, Rungnapa (ASEAN Journal of Education, 2023)
The research objectives consist of the following: (1) to evaluate the efficiency in educational management of academic cooperative project between the Department of Local Administration and Suan Dusit University, (2) to analyze the approaches to improve the inefficiency of educational management of academic cooperative project between the Department of Local Administration and Suan Dusit University and (3) to study the factors that affects the efficiency of educational management of academic cooperative project between the Department of Local Administration and Suan Dusit University. The data was collected by questionnaires and recording forms from the students and instructors in academic cooperative project between the Department of Local Administration and Suan Dusit University. The research results found that there are 4 effective educational centers having efficiency scores of educational management at 100.00. The approaches to improve the inefficiency of educational management of academic cooperative project between the Department of Local Administration and Suan Dusit University is that each educational center should increase 8.98 - 77.89 % of variables. Most of all the inefficiency must be improved by rising the variable of the students’ quality regarding discernment and thinking. Regarding the factors influencing the efficiency of educational management found that the independent variable was academic leadership of the administrators. This significantly affects the efficiency of educational management of academic cooperative project between the Department of Local Administration and Suan Dusit University at .01 level. Thus, the development of academic management of administrators could improve the efficiency of the educational management of the academic cooperative project between the Department of Local Administration and Suan Dusit University.